THE ANALYSIS OF FINANCIAL PERFORMANCE BETWEEN THE MARKET DOMINATING STATE OWNED BANKS AND THE BIG PRIVATE BANKS - Landjang, Xenia I. S.; Tasik, Hizkia H. D. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: There are 117 commercial banks in Indonesian market. According to InfoBankNews.com, the state-owned banks dominated 41.10% of the market based on total assets. This research aims to investigate the financial reasons behind the market domination of the first 4 state-owned banks. This study also makes a comparison to the financial indicators of 4 largest private banks. Panel data regression with fixed effect model is used in this research. The result shows that NPL is one of the underlying reasons behind the domination of the state-owned banks where private banks’ NPL is 3.3 times higher than the state-owned banks’ NPL. Lower NPL in state-owned banks may shed some light on the domination of market share. So, the private banks should decrease the NPL ratio in order to increase their market share.Keywords: financial Performance, non performing loans (NPL), market share, total assets.